2001
DOI: 10.1074/jbc.m010707200
|View full text |Cite
|
Sign up to set email alerts
|

Glucose and Insulin Stimulate Heparin-releasable Lipoprotein Lipase Activity in Mouse Islets and INS-1 Cells

Abstract: Lipoprotein lipase (LpL) provides tissues with triglyceride-derived fatty acids. Fatty acids affect ␤-cell function, and LpL overexpression decreases insulin secretion in cell lines, but whether LpL is regulated in ␤-cells is unknown. To test the hypothesis that glucose and insulin regulate LpL activity in ␤-cells, we studied pancreatic islets and INS-1 cells. Acute exposure of ␤-cells to physiological concentrations of glucose stimulated both total cellular LpL activity and heparin-releasable LpL activity. Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 51 publications
(34 reference statements)
0
45
0
Order By: Relevance
“…Hypertriglyceridemia prioritizing the utilization of TAG as fuels inhibits the intake and oxidization of glucose; 27 intracellular fatty acid metabolites interfere with propagation of insulin signaling cascade; 28 and delivering more FFA to pancreatic b-cells impairs b-cell function and promote apoptosis. 29 The above findings may be partly responsible for the association between LPL and T2D.…”
Section: Lpl and T2dmentioning
confidence: 93%
See 2 more Smart Citations
“…Hypertriglyceridemia prioritizing the utilization of TAG as fuels inhibits the intake and oxidization of glucose; 27 intracellular fatty acid metabolites interfere with propagation of insulin signaling cascade; 28 and delivering more FFA to pancreatic b-cells impairs b-cell function and promote apoptosis. 29 The above findings may be partly responsible for the association between LPL and T2D.…”
Section: Lpl and T2dmentioning
confidence: 93%
“…A recent study found that the reduced LPL delivery in skeletal muscle in skeletal muscle-specific LPL knockout mouse (SMLPLÀ/À) induced increased insulin sensitivity in skeletal muscle but insulin resistance in other metabolic tissues, and ultimately led to obesity and systematic insulin resistance. 29 These results suggested that systematic overexpression of LPL might improve insulin resistance, although the underlying mechanism is not clear. These controversies suggest that the association between the LPL gene and T2D may be tissue specific.…”
Section: Lpl and T2dmentioning
confidence: 97%
See 1 more Smart Citation
“…For these reasons, extracellular NEFA can be expected to rapidly distribute in the available lipid bilayers and to move rapidly from cell to cell, potentially acting as paracrine mediators. In addition, islets express low-density lipoprotein receptors [71] and lipoprotein lipase [72] and could also obtain fatty acids from circulating lipoproteins.…”
Section: Nefa Metabolism In the Beta Cellmentioning
confidence: 99%
“…Second, during in vitro experiments, ␤-cells are exposed to stable, constantly elevated levels of fatty acids, a situation clearly different from the cyclical variations of fatty acid levels that occur in vivo during the prandial cycle. Third, the local concentration of biologically active fatty acids (unbound to albumin) in the vicinity of the ␤-cell is essentially unknown and determined by many factors, including the total fatty acid concentration, the molar ratio of fatty acids to albumin, and the activity of lipoprotein lipase (14).…”
mentioning
confidence: 99%